Sains Dalam Al-Qur'an; Hubungan Antara Al-Qur'an dan Sains Serta Sebagai Upaya Mengenal Tuhan - Rachmah, Nanda Ayu; Fatmawati, Nur Aisyah (Islamic Education Department, Islamic University of Majapahit (Universitas Islam Majapahit) Mojokerto, Indonesia, 2024)
There is no doubt about the relationship between the Al-Qur'an and life, as well as the relationship between Islam and science, which can be said to be very closely related, both in scientific knowledge, which has increasingly been discovered and proven by many scientists, which is It is stated in the Qur'an. This research uses a library research method in the process of collecting data and adapting information related to the relationship between science and the Koran with actual information and from clear sources. Some evidence that proves the truth of the Al-Qur'an is as mentioned in it regarding various natural phenomena and before the universe was formed. Meanwhile, this research discusses the miracles of the Qur'an from a scientific perspective in accordance with the verses of the Qur'an. And these scientific facts have been widely researched by well-known scientists which are in line with what has been explained in the Koran, such as the big bang theory, the characteristics of fingerprints and the development of the fetus in the womb. By studying the importance of the Koran as a source of knowledge in the specifics of modern Islam, it can strengthen the belief of Muslims that in the Koran there are many signs that indicate the greatnss of Allah.